Demobilization and Empire: Empire Nationalism and Soldier Citizenship in Australia After the First World War – in Dominion Context. (January 2015) - Garton, Stephen
This article analyses the demobilization of Australian veterans after the First World War, placing this process in the broader transnational context of Britain's settler society dominions more generally. It explores the public challenges posed by demobilization in Australia, and by way of comparison, Canada, New Zealand and South Africa, and how each of these dominions negotiated reintegration of veterans through the deployment of cultural and political strategies grounded in emergent nationalist discourses. Nationalism became a means of both acknowledging the contribution of veterans in making the nation and tying veterans back into the civil society. While nationalism was the ideological glue that held settler societies together in the immediate postwar years, preventing social and political disintegration, in Australia these nationalist discourses took on a peculiar character, at once proclaiming the virtues of veterans as founders of the nation while adopting a heightened sense of the importance of ties to the Empire. What emerged was a hybrid discourse that interwove nationalism and Empire loyalism, conceptualized here as Empire nationalism. This unusual Australian political discourse was forged by the experience of the Great War and demobilization, grounded in an effort to make soldier citizenship the core foundation for a new nationalism. In Australia Empire nationalism became a framework that both sanctioned particular forms of veteran violence and accommodated that violence into an affirmation of nationalist values, placing the Anzac legend at the centre of the national ethos, one that looked both inward to Australia and backward to Britain.